Application of Data Mining Technology in the Analysis of E-commerce Emotional Law. Issue 2 (April 2021) - Zhang, Shuyue
Abstract: The rapid development of the Internet has brought opportunities for enterprises. Data mining is becoming more and more important in e-commerce websites. In e-commerce, data mining is helpful to discover the development trend of the industry and help enterprises make correct decisions. This paper summarizes the current data mining methods of e-commerce, describes the application of e-commerce website in some data mining applications, classifies its objects, and analyzes the functions of network data mining. It is an important tool to support the experimental research and design of e-commerce system oriented to emotion. The technology of Intelligent Emotion Recognition Based on modern mathematical model and the simulation model of emotion oriented intelligent e-commerce system based on computational intelligence are proposed. For the future of e-commerce practice to provide a reference, especially the development and application of software. The progress in this field is outstanding.